Dynamic Linguistic Interconnectedness and Variability in Toddlers - Petinou, Kakia; Taxitari, Loukia; Phinikettos, Ioannis; Theodorou, Elena (My University, 2021)
This investigation examined the existence of interconnectedness between developing linguistic subsystems. Spontaneous speech samples were collected from 31 typically-developing Greek-speaking toddlers across two age levels, at 28 and 36 months. Correlational analyses were performed synchronically and predictively, revealing significant positive relationships among all language skills within ages. Phonetic and grammatical skills also showed predictive value for later skills. In addition, a cluster analysis on the basis of performance on each individual skill revealed variable linguistic profiles: Low performers showed multiple interactions within and across ages, while High performers showed minimal such interactions. The current results revealed complex interdependencies among the different language skills with children exhibiting variable linguistic profiles, as supported by dynamic systems theory approaches to language acquisition.
Keywords: Dynamic systems theory; Language development; Linguistic interconnectedness